2009
DOI: 10.1519/jsc.0b013e3181874806
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Landing Styles in a Two-Foot Vertical Jump

Abstract: In team sports, such as basketball and volleyball, the players use different takeoff styles to make the vertical jump. The two-foot vertical jump styles have been classified according to the landing style and identified as Hop style, when both feet touch the ground at the same time and Step-close style, when there is a slight delay between the first and second foot making contact with the ground. The aim of this research is to identify the differences between the two styles. Twenty-three subjects participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The CM follows a trajectory with a continuous elevation from TD to TO due to the technical and muscular actions that operate when the foot contacts the board. This behaviour is in agreement with that of other jumping specialities [16][17]. The principal component analysis shows that the jump distance was related to: i) the athlete's approach speed prior to the touch down; and ii) the energy exchange that occurs during the take-off which is intended to gain the maximum vertical velocity of the CM.…”
Section: Discussionsupporting
confidence: 85%
“…The CM follows a trajectory with a continuous elevation from TD to TO due to the technical and muscular actions that operate when the foot contacts the board. This behaviour is in agreement with that of other jumping specialities [16][17]. The principal component analysis shows that the jump distance was related to: i) the athlete's approach speed prior to the touch down; and ii) the energy exchange that occurs during the take-off which is intended to gain the maximum vertical velocity of the CM.…”
Section: Discussionsupporting
confidence: 85%
“…The study also showed that even in the reverse type of „goofy“ approach, there was no relationship between the jump height and vertical impulse, similarly as in other types of take offs, namely the step close jump and the hop jump ( Coutts, 1982 ; Gutierrez-Davila et al, 2009 ). The study emphasizes the importance of the vertical impulse increase during the last two steps regardless of the type of approach, which is in accordance with other studies ( Liu et al, 2001 ).…”
Section: Discussionmentioning
confidence: 77%
“…This test measures the vertical displacement of the center of mass between standing on the ground and at the apex of a jump (31). Jumping primarily involves the gluteal and quadriceps muscles, which are instrumental in many sport and work activities (2,11).…”
Section: Introductionmentioning
confidence: 99%
“…Raw measures of jump height may have some use in performance appraisal, but ideally, an estimate of peak leg power should accompany jump height normative data because this provides insight beyond the outcome of the jump itself (29). For example, 2 individuals of different body weight might be able to jump vertically the exact same distance, therefore calculating power values could provide additional information to that given by jump height alone (11). However, the heavier individuals' jump would show the ability to generate greater power, which could provide an advantage in activities which involve manipulation of mass outside the body (e.g., helping to identify talented athletes).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation